Effect of the Cutting Method and Transport Temperature on the Quality of Ovarian Tissue - Gargallo Alonso, Marta; Chueca, Paula; Pancorbo, Lara; Royo-Cañas, María; Ibáñez-Deler, Alejandro; Malo, Clara (Jornada de Jóvenes Investigadores del I3A, 2025)
This study aimed to assess the impact of different tissue sectioning techniques and transport temperatures on the structural integrity of ovarian tissue. Two primary variables were evaluated: the sectioning method (manual, non-rough surface tool, rough surface tool, and vibratome) and the transport temperature (5°C, 20°C, and 37°C).